СОДРЖИНА НА РИМСКИОТ ТЕСТАМЕНТ - Есин Кранли Бајрам (Институт за правно-економски истражувања и едукација Ј У Р У Д И К А П Р И М А, 2018)
The main aim of this short rewiev is to give a detailed elaboration of the ancientroman testamentum contents. Therefore, on this occasion an analysis will be made of: heredis institutio, substitution and codicillus, which will serveto find the place and the meaning of the aforementioned notions as seen through the prism of the procedure for receiving inheritance and possible consequences which may occur as a result, when some of the obligatory parts of the will, are not included (testamentum nullum, testamentum infirmatum, testamentum destitutum).The concluding observations relating to the basic subject of interest, shed light on the indubitable contribution of the Roman law to the legal inheritance concepts over their modern counterparts, but simultaneously, it also explains the fact that inheritance law, in modern times, has undergone significant changes, conditioned by various socio-economic contexts, which explain why, at times, this law seems a bit different than the one we have inherited from ancient Rome.
Keywords: testamentum, heredis institutio, codicillus.